Analisis proses bisnis kurasi data penelitian di Pusat Data dan Dokumentasi Ilmiah - Seno Yudhanto; Laksmi Laksmi (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. This study aims to identify research data curation activities and business processes at PDDI LIPI Data Collection Methods. This research used a case study approach with interviews and observations of five informants from June to July 2021. Data Analysis Three stages of coding are used to sort, identify, and associate categories with existing theories. Presentation of data was conducted through the description of entities from business processes based on the business process model and notation (BPMN). Results and Discussion. Four main activities of the curation process were carried out. The data owners and curators become actors in the process, and between the two requires trust, communication, and collaboration in their implementation. In addition, validation of the business processes was conducted to show that the process has been running scientifically. Conclusion. The flow of knowledge in these activities is documented in a structured manner based on mapped business procedures and processes. It is necessary to conduct periodic reviews and analyzes of time and resources. Further research should focus on human resources, policy documents, and facilities related to research data curation activities.